Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Find [tex]\( p(0), p(1) \)[/tex], and [tex]\( p(2) \)[/tex] for each of the following polynomials.

(i) [tex]\( p(x) = x^2 - x + 1 \)[/tex]

(ii) [tex]\( p(y) = 2 + y + 2y^2 - y^3 \)[/tex]

(iii) [tex]\( p(z) = z^3 \)[/tex]

(iv) [tex]\( p(t) = (t - 1)(t + 1) \)[/tex]

(v) [tex]\( p(x) = x^2 - 3x + 2 \)[/tex]


Sagot :

Sure, let's evaluate the polynomials step-by-step for [tex]\(x = 0, 1, 2\)[/tex].

### (i) [tex]\( p(x) = x^2 - x + 1 \)[/tex]

1. For [tex]\( x = 0 \)[/tex]:
[tex]\[ p(0) = 0^2 - 0 + 1 = 1 \][/tex]

2. For [tex]\( x = 1 \)[/tex]:
[tex]\[ p(1) = 1^2 - 1 + 1 = 1 \][/tex]

3. For [tex]\( x = 2 \)[/tex]:
[tex]\[ p(2) = 2^2 - 2 + 1 = 4 - 2 + 1 = 3 \][/tex]

Thus, the values are [tex]\( p(0) = 1 \)[/tex], [tex]\( p(1) = 1 \)[/tex], and [tex]\( p(2) = 3 \)[/tex].

### (ii) [tex]\( p(y) = 2 + y + 2y^2 - y^3 \)[/tex]

1. For [tex]\( y = 0 \)[/tex]:
[tex]\[ p(0) = 2 + 0 + 0 - 0 = 2 \][/tex]

2. For [tex]\( y = 1 \)[/tex]:
[tex]\[ p(1) = 2 + 1 + 2 \cdot 1^2 - 1^3 = 2 + 1 + 2 - 1 = 4 \][/tex]

3. For [tex]\( y = 2 \)[/tex]:
[tex]\[ p(2) = 2 + 2 + 2 \cdot 2^2 - 2^3 = 2 + 2 + 8 - 8 = 4 \][/tex]

Thus, the values are [tex]\( p(0) = 2 \)[/tex], [tex]\( p(1) = 4 \)[/tex], and [tex]\( p(2) = 4 \)[/tex].

### (iii) [tex]\( p(z) = z^3 \)[/tex]

1. For [tex]\( z = 0 \)[/tex]:
[tex]\[ p(0) = 0^3 = 0 \][/tex]

2. For [tex]\( z = 1 \)[/tex]:
[tex]\[ p(1) = 1^3 = 1 \][/tex]

3. For [tex]\( z = 2 \)[/tex]:
[tex]\[ p(2) = 2^3 = 8 \][/tex]

Thus, the values are [tex]\( p(0) = 0 \)[/tex], [tex]\( p(1) = 1 \)[/tex], and [tex]\( p(2) = 8 \)[/tex].

### (iv) [tex]\( p(t) = (t-1)(t+1) \)[/tex]

1. For [tex]\( t = 0 \)[/tex]:
[tex]\[ p(0) = (0-1)(0+1) = -1 \cdot 1 = -1 \][/tex]

2. For [tex]\( t = 1 \)[/tex]:
[tex]\[ p(1) = (1-1)(1+1) = 0 \cdot 2 = 0 \][/tex]

3. For [tex]\( t = 2 \)[/tex]:
[tex]\[ p(2) = (2-1)(2+1) = 1 \cdot 3 = 3 \][/tex]

Thus, the values are [tex]\( p(0) = -1 \)[/tex], [tex]\( p(1) = 0 \)[/tex], and [tex]\( p(2) = 3 \)[/tex].

### (v) [tex]\( p(x) = x^2 - 3x + 2 \)[/tex]

1. For [tex]\( x = 0 \)[/tex]:
[tex]\[ p(0) = 0^2 - 3 \cdot 0 + 2 = 2 \][/tex]

2. For [tex]\( x = 1 \)[/tex]:
[tex]\[ p(1) = 1^2 - 3 \cdot 1 + 2 = 1 - 3 + 2 = 0 \][/tex]

3. For [tex]\( x = 2 \)[/tex]:
[tex]\[ p(2) = 2^2 - 3 \cdot 2 + 2 = 4 - 6 + 2 = 0 \][/tex]

Thus, the values are [tex]\( p(0) = 2 \)[/tex], [tex]\( p(1) = 0 \)[/tex], and [tex]\( p(2) = 0 \)[/tex].

In summary, here are the results for each polynomial:

1. [tex]\( p(x) = x^2 - x + 1 \)[/tex]:
[tex]\[ p(0) = 1, \quad p(1) = 1, \quad p(2) = 3 \][/tex]

2. [tex]\( p(y) = 2 + y + 2y^2 - y^3 \)[/tex]:
[tex]\[ p(0) = 2, \quad p(1) = 4, \quad p(2) = 4 \][/tex]

3. [tex]\( p(z) = z^3 \)[/tex]:
[tex]\[ p(0) = 0, \quad p(1) = 1, \quad p(2) = 8 \][/tex]

4. [tex]\( p(t) = (t-1)(t+1) \)[/tex]:
[tex]\[ p(0) = -1, \quad p(1) = 0, \quad p(2) = 3 \][/tex]

5. [tex]\( p(x) = x^2 - 3x + 2 \)[/tex]:
[tex]\[ p(0) = 2, \quad p(1) = 0, \quad p(2) = 0 \][/tex]